Rapid and Highly Efficient Genetic Transformation and Application of Interleukin-17B Expressed in Duckweed as Mucosal Vaccine Adjuvant - Xiao Tan; Shuang Chen; Yang Fang; Penghui Liu; Zhubin Hu; Yanling Jin; Zhuolin Yi; Kaize He; Xing Li; Leyi Zhao; Hongning Wang; Hai Zhao (Biomolecules, 2022)
Molecular farming utilizes plants as a platform for producing recombinant biopharmaceuticals. Duckweed, the smallest and fastest growing aquatic plant, is a promising candidate for molecular farming. However, the efficiency of current transformation methods is generally not high in duckweed. Here, we developed a fast and efficient transformation procedure in Lemna minor ZH0403, requiring 7–8 weeks from screening calluses to transgenic plants with a stable transformation efficiency of 88% at the DNA level and 86% at the protein level. We then used this transformation system to produce chicken interleukin-17B (chIL-17B). The plant-produced chIL-17B activated the NF-κB pathway, JAK-STAT pathway, and their downstream cytokines in DF-1 cells. Furthermore, we administrated chIL-17B transgenic duckweed orally as an immunoadjuvant with mucosal vaccine against infectious bronchitis virus (IBV) in chickens. Both IBV-specific antibody titer and the concentration of secretory immunoglobulin A (sIgA) were significantly higher in the group fed with chIL-17B transgenic plant. This indicates that the duckweed-produced chIL-17B enhanced the humoral and mucosal immune responses. Moreover, chickens fed with chIL-17B transgenic plant demonstrated the lowest viral loads in different tissues among all groups. Our work suggests that cytokines are a promising adjuvant for mucosal vaccination through the oral route. Our work also demonstrates the potential of duckweed in molecular farming.